Tourism Destination Development Strategy Using The 4A Framework: Evidence from Klayar Beach, Indonesia - Saputra, Reno Adi; Indahsari, Kurniyati; Sugiarti, Sugiarti (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2026)
This study aims to formulate tourism development strategies for Klayar Beach in Pacitan Regency, East Java Province, Indonesia, which has experienced a decline in tourist arrivals over the past three years. A mixed-methods approach was employed. Qualitative data were collected through in-depth interviews, documentation, and a literature review to identify the internal and external factors influencing destination management, based on the 4A tourism development framework, which consists of attraction, accessibility, amenities, and ancillary services. Subsequently, SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis and Internal–External Factor Analysis Summaries (IFAS–EFAS) were conducted to formulate priority tourism development strategies. The integration of the 4A framework with a mixed-methods approach represents the novelty of this study in identifying priority strategies for tourism destination development. The findings reveal that Klayar Beach's primary strengths lie in its unique natural attractions and the active involvement of the local community in destination management. However, its main weaknesses include inadequate tourism facilities, limited accessibility, and underdeveloped supporting services. The major opportunities for tourism development arise from the increasing demand for nature-based tourism experiences, the potential to develop thematic tourism packages, and strong support from both the government and private sectors in promoting tourism as a driver of regional development. Conversely, visitor safety risks and the growing competition from similar coastal tourism destinations pose significant threats. Based on the results of the SWOT and IFAs–EFAs analyses, Klayar Beach's development strategy is positioned in the aggressive (SO) quadrant, indicating that it should capitalize on existing strengths to seize available opportunities. Therefore, this study recommends optimizing tourism attractions, developing thematic tourism packages, strengthening Community-Based Tourism (CBT) management, and enhancing collaboration with local MSMEs and other stakeholders to sustainably increase tourist arrivals. Keywords: Tourism Development Strategy; 4A Tourism DevelopmentFramework; SWOT Analysis; Internal–External Factor Analysis Summary (IFAS–EFAS)